2019
DOI: 10.13057/biodiv/d201236
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and host preferences of ferns and lycopods epiphytes on palm trees

Abstract: Abstract. Praptosuwiryo TN, Sumanto, Cahyaningsih. 2019. Diversity and host preferences of ferns and lycopods epiphytes on palm trees. Biodiversitas 20: 3731-3740. Epiphytic ferns contribute importantly to the global biodiversity of tropical rain forests. However, our knowledge of the ecology of epiphytic ferns is phenomenally still limited. Most studies on the ecology, floristic and diversity of epiphytic ferns and lycopods were reported outside of Malesian region. This study aimed: (i) to figure out the dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…2 and Table 1). The floristic composition of the epiphyte community is similar to those found on palm trees growing in BBG with 16 species of epiphytic ferns and lycopods (Praptosuwiryo et al 2019). The highest species richness was recorded in Polypodiaceae with seven species.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…2 and Table 1). The floristic composition of the epiphyte community is similar to those found on palm trees growing in BBG with 16 species of epiphytic ferns and lycopods (Praptosuwiryo et al 2019). The highest species richness was recorded in Polypodiaceae with seven species.…”
Section: Resultssupporting
confidence: 62%
“…Previous publications stated that the epiphytic ferns flora holo-epiphytes are usually predominant (Fraga et al 2008 andSchmitt 2011) in Brazil;and Praptosuwiryo et al (2019) in BBG. Some epiphytes also grow occasionally on rocks, such as Belvisia mucronata and Microsorum scolopendria (Hovenkamp et al 1998), or soil such as Nephrolepis biserrata (Xing et al 2013) and Psilotum nudum (Zhang and Yatskievych 2013).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Both extracts were classified as having strong antioxidants. Praptosuwiryo et al (2019) found that N. biserrata tends to grow abundantly on palm trees plantation especially on upper zone of trees. Besides, it useful to maintain the land humidity and keep the soil from lack of water (Ariyanti 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Two particularly curious observations of accidental epiphytism were reported from moist deciduous forests in northeastern India, where the banana species Musa acuminata (Deb et al, 2018) and the bamboo species Bambusa tulda (Majumdar et al, 2012) were growing in tree cavities. Moreover, across tropical Asia, accidental epiphytism was observed in various ecosystems, for example, in tropical montane forests of southern India (Mathew, 2013), in agricultural plantations such as tea plantations (Ohsawa, 1982) or oil palm plantations (Böhnert et al, 2016;Nadarajah & Nawawi, 1993;Prescott et al, 2015), at urban roadside trees in Singapore (Izuddin & Webb, 2015), or in botanical gardens in Indonesia (Junaedi & Nasution, 2018;Praptosuwiryo et al, 2019).…”
Section: Global Occurrences Of Accidental Epiphytesmentioning
confidence: 99%